Skuteczność wykorzystania nowoczesnych metod zarządzania w kierowaniu zmianami - Skalik, Jan (Effectiveness of Application of Modern Management Methods in Implication of Changes, 2006)
The success of modern organizations depends on effective implementation of aptly chosen changes, which often demands application of modern management methods. The conditions of proper and effective selection of managerial tools, which take into account the fulfillment of utilitarian criteria as well as expectations associated with guarantee of managerial sovereignty of organization, were described in this paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 130-134